СHILDREN OF MEGAPOLISES WHO FALL ILL FREQUENTLY: ACUTE RESPIRATORY INFECTION PREVENTION AND TREATMENT - R.M. Torshkhoeva; V.V. Botvin'eva; T.G. Tagi-zade; L.S. Namazova; T.E. Taranushenko (Педиатрическая фармакология, 2006)
The article is devoted to prevention and treatment of acute respiratory diseases children of megapolises who fall ill frequently. The authors prove the thesis that children falling ill frequently and residing in mega cities, and not only in Russia, have a similar immune status, according to which not only therapeutic but also preventive immunomodulatory treatment courses must be administered to them.Key words: frequently ill children, bacterial immunomodulation, cytokinic status.